Uterine arteriovenous malformation leading to postpartum hemorrhage: A case report - Nathaniel Gallagher; Matthew Cincotta; Hisham Keblawi; David Jude; Michael Korona (Elsevier, 2020)
Uterine arteriovenous malformation (AVM) is an uncommon but potentially life-threatening cause of postpartum hemorrhage (PPH). AVMs often present with intermittent or profuse vaginal bleeding in a woman with a history of uterine instrumentation. Transvaginal ultrasound is the initial imaging method used for diagnosis. Management depends on the patient's hemodynamic stability and desire for future pregnancy. Uterine artery embolization (UAE) is the initial treatment option for women of reproductive age. Due to limited evidence, there are no guidelines for the management of failed UAE. Here we report a case of uterine AVM following a cesarean section that failed initial management with UAE and required emergency hysterectomy.